COMPUTER MODELING USING THE AUTODESK 3D STUDIO MAX EDITOR - Turganbayeva А.Р.; Bolysbekova Ф.Қ. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
This article describes in detail the capabilities of the Autodesk 3D Studio Max editor, which allows secondary school students to master three-dimensional computer modeling. To do this, we selected and studied modeling methods that allow us to create models of various complexity. The article provides modules and operators that can create part models and create real-world effects, create relationships between parts, and combine parts with each other and other objects. We studied the well-known visualization tools for working with three-dimensional graphics Autodesk 3D Studio Max. As a result of the experiment, it was proved that this platform is popular due to a wide range of features that facilitate the creation of complex 3D objects and scenes. It turned out that the Autodesk FBX cross-platform was designed to create 3D data and share it. It provides access to 3D models created in most third-party systems. Conclusions were made that it is available for high school students to master.